Inhaled Surfactant Therapy in Newborns in Artificial Lung Ventilation - S. A. Perepelitsa; A. A. Luchina (Общая реаниматология)
Objective: to evaluate the efficiency of inhaled surfactant therapy in neonatal infants with respiratory failure.Subjects and methods. The trial enrolled 13 premature neonatal infants; their mean gestational age was 31.8±2.8 weeks and the birth weight was 1825±600.9 g. They had a oneminute Apgar score of 4.3±1.4. All the neonates needed mechanical ventilation (MV) atbirth because the leading clinical sign was respiratory failure caused by acute intranatal hypoxia, neonatal amniotic fluid aspiration, respiratory distress syndrome (RDS), and cerebral ischemia. Curosurf was injected in a dose of 174.7±21 mg/kg in the infants with neonatal RDS at 35 minutes of life. All the babies included in the study were noted to have severe disease and prolonged MV. After stabilization of their status, the neonates received combination therapy involving surfactantBL inhalation to reduce the duration of MV. The dose of the agent was 75 mg. Results. After surfactantBL inhalation, effective spontaneous respiration occurred in 69.2% of the newborn infants; successful extubation was carried out. The median duration ofMV after surfactant BL inhalation was 22 hours (4—68 hours). There were no reintubated cases after inhalation therapy. Following surfactantBL inhalation, 4 (30.8%) patients remained to be on MV as a control regimen; 3 of them had highfre quency MV. SurfactantBL inhalation made it possible to change the respiratory support regimen and to reduce MV parame ters in these babies.